Determination of arsenic, cadmium, mercury and lead in Oncorhynchus mykiss from fish farms in Junin-Peru, 2021 - Palacios-Lozano, Anali Anyela (2025)
Anthropogenic activities are exerting increasing pressure on aquatic ecosystems, leading to contaminación by heavy metals. This study aimed to determine the concentrations of arsenic (As), cadmium (Cd), mercury (Hg), and lead (Pb) in rainbow trout (Oncorhynchus mykiss) from fish farms in the districts of Ingenio, Miraflores, and Chongos Alto, province of Huancayo – Junín, Perú (2021). A total of 12 samples (four per district) were analyzed at Actlabs laboratory. Heavy metal concentrations were determined using atomic absorption spectrometry with a graphite furnace (GF-AAS) for Pb and Cd, and a hydride generator (HG-AAS) for As and Hg. Permissible limits established by MERCOSUR and SANIPES were considered as reference values. Results showed concentrations of As (0.98, 1.02, and 0.76 mg/kg), Cd (0.06, 0.04, and 0.03 mg/kg), Hg (0.57, 0.44, and 0.46 mg/kg), and Pb (0.35, 0.25, and 0.31 mg/kg) in Ingenio, Miraflores, and Chongos Alto, respectively. Arsenic levels were within permissible limits in all districts. However, in Ingenio, Cd, Hg, and Pb exceeded the regulatory thresholds, highlighting a higher contamination risk in this area.